2018
DOI: 10.1101/358663
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FtsW is a peptidoglycan polymerase that is activated by its cognate penicillin-binding protein

Abstract: 12The peptidoglycan cell wall is essential for the survival and shape maintenance of 13 bacteria. 1 For decades it was thought that only penicillin-binding proteins (PBPs) 14 effected peptidoglycan synthesis. Recently, it was shown that RodA, a member of the 15 Rod complex involved in side wall peptidoglycan synthesis, acts as a peptidoglycan 16 polymerase. [2][3][4] RodA is absent or dispensable in many bacteria that contain a cell wall; 17 however, all of these bacteria have a RodA homologue, FtsW, which is … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…FtsW has been shown to form a ternary complex with PBP3 and PBP1b, and the lipid II binding activity of FtsW inhibits the polymerization of lipid II by PBP1b in the absence of PBP3, while the presence of PBP3 stimulates the release of lipid II from FtsW, and activates its polymerization by PBP1b (Leclercq et al, ). In addition, new evidence supports glycosyltransferase activity for FtsW (Taguchi et al, ). These observations raised the possibility that FtsW activity is needed to ensure MurJ localization.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…FtsW has been shown to form a ternary complex with PBP3 and PBP1b, and the lipid II binding activity of FtsW inhibits the polymerization of lipid II by PBP1b in the absence of PBP3, while the presence of PBP3 stimulates the release of lipid II from FtsW, and activates its polymerization by PBP1b (Leclercq et al, ). In addition, new evidence supports glycosyltransferase activity for FtsW (Taguchi et al, ). These observations raised the possibility that FtsW activity is needed to ensure MurJ localization.…”
Section: Resultsmentioning
confidence: 86%
“…FtsW has been shown to form a ternary Chromosomal mNG-(GGS) 2 -MurJ fusion was introduced into strains that harbor temperature sensitive, depletable or deleted division proteins (except that the mNG-(GGS)2-MurJ was expressed in ΔtolA and Δpal strains from plasmid pXL05, and mCherry-MurJ was expressed in ΔamiABC strain from plasmid pNM037 (Leclercq et al, 2017). In addition, new evidence supports glycosyltransferase activity for FtsW (Taguchi et al, 2018). These observations raised the possibility that FtsW activity is needed to ensure MurJ localization.…”
Section: Murj Midcell Localization Requires Ftsw Activitymentioning
confidence: 99%
“…Interestingly, the essential function of PBP1 is not dependent on its transpeptidase activity, suggesting that this protein has a second function. While writing this manuscript, preprint data from the Walker laboratory demonstrated that S. aureus PBP1 stimulates the essential TG activity of FtsW, independently of its TP active site 12 , which could explain the essentiality of PBP1. This regulation of the activity of SEDS proteins and bPBPs may be essential to avoid the synthesis of uncrosslinked glycans 27 , which has been shown to lead to a toxic futile cycle of glycan synthesis and degradation in E. coli 28 .…”
Section: Ormentioning
confidence: 99%
“…Some bacteria also have monofunctional glycosyltransferases (MGTs), enzymes with a TG domain with homology to the TG domain of aPBPs 10 . More recently, RodA and FtsW, members of the shape, elongation, division and sporulation (SEDS) protein family, were also shown to have transglycosylase activity [11][12][13] .…”
mentioning
confidence: 99%
“…FtsW, a RodA homolog and a key component of the divisome machinery, forms a complex with FtsI (PBP3), which has been shown to interact with PBP1b, FtsN and other proteins of the divisome 34 . The FtsW-PBP3 complex shares similar interacting regions with the RodA-PBP2 complex, and is the confirmed PG polymerase of the divisome 35 .…”
Section: Introductionmentioning
confidence: 61%